ALCOHOL ABUSE IN RURAL AREAS OF PUNJAB (INDIA) - SHARMA, SUMAN; MINHAS, DEEPTI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Alcohol consumption has shown a considerable rise over the last couple of years. There is hardly any social function which is considered complete without a liberal supply of alcohol. Today most of the alcohol users are introduced to hard liquor at a much earlier age which gives them a long span of alcohol consumption. They are at much higher risk of developing various psychological and physical complications. In the present study, total of 150 male subjects from rural areas of the district Hoshiarpur, Punjab (India) has been surveyed. Alcohol drinkers were divided into light, moderate and heavy drinkers on the basis of amount of alcohol consumption. The subjects were ¡nterviewed personally using the questionnaire to get the information regarding various aspects of subjects like general information, history of drinking habit, current patterns of alcoholism, dietary intake etc. Alcohol consumption was found to be more prevalent in married people and it is a’so found to be common among undergraduates.